The Concept of Buraq in the Events of Isra’ Mi'raj: Literature and Physics Perspective - Himatul Istiqomah; Muhammad Ihsan Sholeh (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Isra’ Mi'raj is one of the greatest phenomena that happened to the Prophet Muhammad PBUH after his beloved wife, Khadijah al-Kubra, passed away. It was told that when this event occurred, the Prophet Muhammad PBUH used Buraq during his journey from the Masjidil Haram, Makkah to the Masjidil Aqsha, Palestine, and when he ascended to Sidratul Muntaha. This research applied a descriptive qualitative method with a literature study. The results of this study indicate that there are two versions of the explanation about Buraq. From the literature’s perspective, the Buraq is visualized as a riding animal in the form of a four-legged animal that has high speed. This perspective is aimed at audiences from the non-academic community. Whereas,according to the physicist's perspective, Buraq is explained as a light which indeed has very high speed. This perspective is aimed at audiences from the academic community